An Overview of Venous Abnormalities Related to the Development of Lesions in Multiple Sclerosis - Haacke, E. Mark; Ge, Yulin; Sethi, Sean K.; Buch, Sagar; Zamboni, Paolo (Frontiers in Neurology, 2021)
The etiology of multiple sclerosis (MS) is currently understood to be autoimmune. However, there is a long history and growing evidence for disrupted vasculature and flow within the disease pathology. A broad review of the literature related to vascular effects in MS revealed a suggestive role for abnormal flow in the medullary vein system. Evidence for venous involvement in multiple sclerosis dates back to the early pathological work by Charcot and Bourneville, in the mid-nineteenth century. Pioneering work by Adams in the 1980s demonstrated vasculitis within the walls of veins and venules proximal to active MS lesions. And more recently, magnetic resonance imaging (MRI) has been used to show manifestations of the central vein as a precursor to the development of new MS lesions, and high-resolution MRI using Ferumoxytol has been used to reveal the microvasculature that has previously only been demonstrated in cadaver brains. Both approaches may shed new light into the structural changes occurring in MS lesions. The material covered in this review shows that multiple pathophysiological events may occur sequentially, in parallel, or in a vicious circle which include: endothelial damage, venous collagenosis and fibrin deposition, loss of vessel compliance, venous hypertension, perfusion reduction followed by ischemia, medullary vein dilation and local vascular remodeling. We come to the conclusion that a potential source of MS lesions is due to locally disrupted flow which in turn leads to remodeling of the medullary veins followed by endothelial damage with the subsequent escape of glial cells, cytokines, etc. These ultimately lead to the cascade of inflammatory and demyelinating events which ensue in the course of the disease.